About determination of contact parameters by dynamic co-operation of sphere and plane by a power method - Маковкін, О.М.; Диха, М.О.; Дитинюк, В.О. (Problems of Tribology, 2016)
Power approach for determination of blow force at co-operation of resilient sphere and plane on the basis of experimental information about the sizes of ground of contact is offered. After the got value of force of blow the expected values of middle and maximal pressure. Offered calculation-experimental a method is extended on the contact of bodies of bicurvature with the use of method of similarity.